Нетреба в археологічному літописі України - Горбаненко, С.А. (Археологія, 2022)
У статті зібрано й упорядковано дані про знахідки нетреби звичайної (Xanthium strumarium L.) на
пам’ятках території сучасної України. Перша знахідка (Більськ) походить із випадкового зразка; ще
дві представлені відбитками на виробах із глини. Їх
виявлено у процесі цілеспрямованого огляду кераміки, що походить із пам’яток скіфського часу. Ще
дві знахідки знайдено на давньоруських пам’ятках,
де зібрано обгорілий матеріал. Територія сучасної
України розташована на роздоріжжі сухопутних і
водних шляхів Євразії, отже, представлені знахідки
важливі для відновлення історії поширення нетреби звичайної на території Європи. In the article, data on common cocklebur (Xanthium strumarium L.) finds from the archaeological sites of modern Ukraine is
collected and organized. Three of them come from the Scythian period sites. The first find (Bilsk, Poltava Oblast) comes from
random sample. Two more finds (Tsyrkuny and Novoselivka, Kharkiv Oblast) are represented by prints on clay objects. They
were discovered as a result of a purposeful inspection of ceramics in order to search for palaeoethnobotanical materials. Two
other items were found on ancient Rus sites, where burnt material was collected. In the first case (Manzheliia, Poltava Oblast)
the material was examined during the classical excavations. Palaeoethnobotanical remains were in clearly visible accumulations.
In the second case (Peresopnytsia, Rivne Oblast) the material was obtained by soil flotation.
The territory of modern Ukraine is located at the crossroads of land routes and waterways of Eurasia. It is a part of the path
of constant migration from Asia to Europe. We can assume that at least in the early Iron Age, due to the nomads, the common
cocklebur had already reached the territory of modern Ukraine. The earlier appearance of this plant in the area can be considered
purely hypothetically, only on the grounds that in the western territories it was discovered at the sites of the end of the Bronze
Age / beginning of the Early Iron Age.
According to isolated materials from the Scythian period sites and from ancient Rus dwellings in Peresopnytsia, it is difficult
to assume something about the use of common cocklebur. According to the materials from Manzhelia (several dozens of fruits),
it is possible to presume purposeful collecting of cocklebur, probably as a medicinal plant.
The presented findings are important for the restoration of the penetration history of common cocklebur into Europe.